PEMBERDAYAAN MASYARAKAT : PELATIHAN KADER KESEHATAN MENANGANI KEGAWATDARURATAN ANAK DAN DEWASA - Setiawati setiawati; Dhiny Easter Yanti; Linawati Novikasari; Agung Julian Pangestu; Hikmah Nurapiansyah (Jurnal Abdi Masyarakat, 2024)
Emergency conditions involve health facility preservers to provide first aid. Lampung is in the ring of fire area. The incidence of disasters in 2023 increased compared to 2022, BNPB recorded 5,400 disaster events Throughout 2023, there were 148,307 accidents throughout Indonesia and there were 96 natural disasters in Bandar Lampung City during 2023 and dominated by floods and fallen trees. Cadres as the spearhead of health services in the community, should have the knowledge and skills to provide help to the community who experience emergency events. The method of implementation is RRA. Socialization and training using manuals, presentations with power points and demonstrations, with equipment: P3K kits, stretchers, spalks, mulch. The training participants were 26 000 health cadres. The results of the mean difference test obtained a value of p.value = 0.001, meaning that there was a difference in the mean before and after the training. The team suggested that in the future it can make activity media in the form of video applications to make it easier for cadres to access.